Molecular characterization of fire ants, Solenopsis spp., from Brazil based on analysis of mtDNA gene cytochrome oxidase i - Martins, Cintia; Souza, Rodrigo Fernando De [UNESP]; Bueno, Odair Correa [UNESP] (Oxford University Press (OUP), 2014)
Species from the Solenopsis saevissima (Smith) (Hymenoptera: Formicidae) species group are native to South America and have a cosmopolitan distribution because they have been accidentally introduced in many countries around the world. In Brazil, they have a wide distribution, including urban areas. The present study was conducted to investigate the characterization of Solenopsis genus populations associated with urban/human interference sites in Brazil by analyzing the mitochondrial gene cytochrome oxidase I and estimating the degree of relatedness of these populations to make inferences about their phylogeny and also observe the patterns of mitochondrial haplotype (mitotype) distribution across their range. The results revealed complete geographical coherence and polyphyly for the Solenopsis invicta Buren and Solenopsis saevissima species groups, which confirms the diversity of the genera. It also suggests the possibility that reproductively-isolated populations occur, resulting in the evolutionary process of speciation. No predominant haplotype was found in the populations analyzed, but some were more prevalent. © This is an open access paper. We use the Creative Commons Attribution 3.0 license that permits unrestricted use, provided that the paper is properly attributed.
Keywords: mitochondrial DNA; phylogeny; Solenopsis invicta; Solenopsis saevissima